A Blockchain Based Online Business Intelligence Learning System - Po Abas Sunarya; Alexander Williams; Alfiah Khoirunisa; Adrian Sean Bein; Delfi Martika Sari (Blockchain Frontier Technology, 2021)
It isn't an smooth challenge for instructors to test day by day scholar mastering assignments and deliver appropriate grades, attitudes each day. Online mastering structures are nevertheless prone and effortlessly added with the aid of using instructors and gadget managers. Blockchain offers everlasting and dependable garage offerings in addition to computerized calculation offerings. Therefore, the blockchain-primarily based totally on-line mastering gadget proposed on this paper, serves to examine the day by day lives of college students and mechanically their attitudes if you want to relieve instructors from tedious and complicated workloads and may offer sincere and accurate opinions of scholar attitudes. This article uses a qualitative method. Therefore, this text introduces the state of affairs of mastering commercial enterprise intelligence in universities and jobs associated with blockchain-primarily based totally commercial enterprise intelligence mastering structures. Then the gadget is exact withinside the shape and clever contracts.